Sandwich structural panels comprising thin-walled SFRSCC and GFRP connectors: from material features to structural behaviour - Lameiras, Rodrigo Melo (2016)
Tese de Doutoramento em Engenharia Civil (Especialização em Engenharia de Estruturas).